UTILITY OF ELECTROPHORESIS IN NURSERY MANAGEMENT STRATEGY: IMPACT OF FERTILIZERS ON ZOOPLANKTON SUCCESSION AND GROWTH OF CIRRHINUS MRIG ALA (HAM.) - Jayapala, P; Rajbanshi, V K; Sharma, L L; Sharma, O P (Indian Journal of Fisheries, 2011)
While many factors may influence the survival of spwan, there is a strong evidence that lack of zooplankton in sufficient quantity may be a major cause of their mortality (Jhingran, 1983)